Ethnofestivals in Chernivtsi Region as Indicators of Polyethnic Identity and Components of Community Development Potential - Kisil, Roman (Human Geography Journal, 2023)
This article examines the spatio-temporal (historical-geographical) features of holding ethnofestivals in the Chernivtsi region, which are important indicators of its features such as polyethnicity and ethno-contact. Such events not only celebrate the cultural heritage of various ethnic communities living in the region but also serve as significant indicators of the ethno-cultural potential for the development of individual settlements, territorial communities, territories, and the region as a whole. It is also worth emphasizing the importance of holding ethnofestivals in the cross-border region, as it expands the inflow of investments into the region, as well as the possibility of jointly organizing such events between Ukraine, Romania, and Moldova.Many ethnocultural festivals of poetic, ethnographic, artistic, spiritual, gastronomic, and other directions are held in the Chernivtsi region. The largest number of ethnofestivals is held in the regional center – the city of Chernivtsi. However, due to the COVID-19 pandemic, which has been ongoing since March 2020, and immediately after the start of a full-scale war with the Russian Federation, the number of held ethnofestivals has decreased significantly. Festivals such as "Bukovynska Malanka" ("Malanka Fest"), the ethno-spiritual festival "Onova-fest", "International Hutsul Festival", "Colors of Storozhinechchyna", and others were practically not held in those years. However, despite the difficulties, ethnofestivals like the ethno-festival of theatrical art "Golden Applause of Bukovyna", the poetry festival "Meridian Czernowitz", "Tulip Field", "Pumpkin Field", and others are still being held.Each ethnographic festival has its own characteristics of being held both in Ukraine in general and in the region in general, which relate not only to the venue, meaningful content, but also to the peculiarities of the terrain and weather conditions, seasonality of the climate. Another important factor is the number of festivals and the ability of the infrastructure to meet the needs of tourists.It should be noted that each ethnofestival held in the Chernivtsi region is primarily aimed at uniting different ethnic groups of the population of the multi-ethnic region, as well as popularizing the material and spiritual culture, ethno-landscapes of Northern Bukovina, and Northern Bessarabia. Ukrainians, Romanians, and Moldovans, who have compact settlements in the region, are the most active in holding ethnofestivals, which gives reason to call the region an ethno-contact area.